2020
DOI: 10.1055/s-0040-1705136
|View full text |Cite
|
Sign up to set email alerts
|

Growth from Birth to 30 months for Infants Born with Congenital Gastrointestinal Anomalies and Disorders

Abstract: Objective This study aimed to investigate growth among neonates with gastrointestinal disorders. Study Design Inclusion criteria included neonates with gastroschisis, omphalocele, intestinal atresia, tracheoesophageal fistula, Hirschsprung's disease, malabsorption disorders, congenital diaphragmatic hernia, and imperforate anus born between 2010 and 2018. Anthropometrics were collected for the first 30 months, and a subgroup analysis was performed for gastroschisis infants. Results In 61 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
8
0
3
Order By: Relevance
“…Research showed [3] that infants with gastrointestinal tract abnormalities (including IA) had a risk of around 13% for growth retardation. In this study, 4 cases had both age-speci c weight and height <-2 SD, 2 cases had age-speci c weight <-2 SD, and 6 cases had age-speci c height <-2 SD.…”
Section: Discussionmentioning
confidence: 99%
“…Research showed [3] that infants with gastrointestinal tract abnormalities (including IA) had a risk of around 13% for growth retardation. In this study, 4 cases had both age-speci c weight and height <-2 SD, 2 cases had age-speci c weight <-2 SD, and 6 cases had age-speci c height <-2 SD.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants with a birth weight <1500 g and a gestational age <32 weeks of gestation were included. Excluded were all infants with diseases affecting stable growth (i.e., necrotizing enterocolitis (NEC) with short bowel syndrome [ 21 ], Hirschsprung disease [ 22 ], chronic inflammatory bowel disease [ 23 ], bronchopulmonary dysplasia (BPD) [ 24 ], congenital heart disease [ 25 ], major congenital birth defects or chromosomal aberrations).…”
Section: Methodsmentioning
confidence: 99%
“…The study design and the primary outcome were recently published [13]. Inclusion criteria were a gestational age <32 weeks of gestation and a birth weight <1500 g. Infants with diseases affecting stable growth, i.e., necrotizing enterocolitis (NEC) with short bowel syndrome [14], Hirschsprung disease [15], chronic inflammatory bowel disease [16], bronchopulmonary dysplasia (BPD) [17], congenital heart disease [18], or major congenital birth defects or chromosomal aberrations were not eligible. Parents of infants were contacted at the outpatient clinic at their expected date of birth and randomized to an early complementary feeding group with an introduction of solid foods between the 10th and 12th week of life corrected for term compared to a late complementary feeding group with an introduction of complementary food between the 16th and 18th week of life corrected after informed consent was obtained from the parents.…”
Section: Methodsmentioning
confidence: 99%